Potensi Damar Indonesia Sebagai Bahan Baku Material Kedokteran Gigi - Kosterman Usri; Elin Karlina; Veni Takarini (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2020)
One of the natural resins in the world market which is dominated by production from Indonesia is damar. Damar is a resin produced by the Shorea javanica tree. This resin is known to have the best quality compared to other types of resin. In Indonesia, this plant grows well in Sumatra, Kalimantan, Sulawesi, and Maluku, but is mainly produced in the Krui Coastal area of Lampung in an agroforest system known as Repong Damar. From the Shorea javanica tree, two types of resin are produced, namely damar mata kucing and damar batu. Damar mata kucing is obtained by tapping while rock resin is obtained by picking up resin which drips naturally onto the ground. The resin quality standard is stipulated in the Standar Nasional Indonesia (SNI) 2900.1:2012 for visual test and SNI 2900.2:2013 for for laboratory tests. Resin has properties in accordance with the requirements of dental materials, such as white to yellow colour, non-volatile, and insoluble in water. But it also has unsuitable properties such as brittle, sticky at room temperature, not heat resistant, flammable, and will change color when stored for a long time. It is concluded that resin modification has the potential to be used as raw material for dentistry, but it needs to be modified and its mechanical properties need to be tested.